Cooling supply costs of a university campus. (15th June 2022) - Schüppler, Simon; Fleuchaus, Paul; Duchesne, Antoine; Blum, Philipp
Abstract: Global climate change and growing research activities lead to increasing cooling demands and related supply costs at universities, while at the same time ambitious goals towards carbon neutral campuses are established. Hence, universities are facing the challenge to develop large scale future-proof cooling solutions. This also applies to the Campus North of the Karlsruhe Institute of Technology (KIT), where the current cooling supply, consisting of decentralized rooftop compression chillers, is insufficiently monitored resulting in a lack of knowledge on supply costs and cooling needs of each facility. Hence, the objective of this study is to examine the current cooling supply and related cost by the analysis of 47 compression chillers supplying 23 buildings at the campus. To compensate for the given uncertainties of the provided input parameters, a Monte Carlo simulation is performed revealing cooling costs ranging between 5.4 and 11.4 eurocent per kWh. The overall supplied energy and installed cooling capacity amount to 70 GWh and 20 MW, respectively. Cumulative annual costs of 4.5 € million, mainly resulting from the electricity costs to power the chillers, request for a transition to a decentralized and more efficient cooling supply by integrating renewable cooling supply solutions. Highlights: Straightforward approach to determine cooling supply costs on campus level. Consideration of investment, demand and operation-related costs of 47 chillers. Cooling supply costs of the chillers range between 5.4 and 11.4 eurocent kWh −1 . The cooling demand and total costs of the study area are 70 GWh and 4.5 € million. Renewable district cooling concepts can reduce the demand-related costs by 80%.